Good Literacy to Enhance Response in Diabetes Mellitus (GLITTER-DM) - Yen Dang; Nima Patel-Shori; Michael Barros; Daohai Yu (University of Minnesota Libraries Publishing, 2020)
Objective: The purpose of this study is to determine the effectiveness of individualized communication strategies and self-management action plans to improve A1c control at 3 months in patients with low health literacy. Methods: A prospective, open-labeled, pilot study was conducted on 23 patients with diabetes mellitus in a pharmacist-led ambulatory care clinic. Patients who had a Rapid Estimate of Adult Literacy in Medicine- Revised (REALM-R) score of 6 or less and an A1c greater than 7% upon study entry were included. The first group received the teach-back method, personalized actions, and follow-up phone calls to assess comprehension (N = 12). The second group was assigned to usual care (N = 11). Results: Patients receiving literacy-appropriate interventions had greater A1c percent reduction (A1c difference of -2.0 ± 1.3 vs -1.0 ± 2.2; P = 0.02) and less hyperglycemic events per week (0.1 vs. 2.1; P = 0.04). There were no differences in the number of hypoglycemic events, testing frequency, medication-adherence rates, or hospitalizations and emergency room visits related to diabetes. Conclusion: Literacy-appropriate methods such as the teach-back method, personalized action plans, and telephone follow-ups may improve glycemic control in low health literate patients with diabetes. Practice Implications and Innovations: The findings from this study suggest that pharmacists may improve diabetes outcomes when managing patients who possess low health literacy using simplified teaching methods.   Original Research